Interrupted PET coupled TBET process for the design of a specific receptor for Hg2+ and its intracellular detection in MCF7 cells - Saha, Sukdeb; Mahato, Prasenjit; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2012)
A new coumarin–rhodamine conjugate constitutes a unique example of the interrupted PET coupled TBET response for developing an imaging reagent for determining the intracellular distribution of Hg2+ in MCF7 cells exposed to [Hg2+] as low as 2 ppb.